Analisis Perbandingan Konsep Imkān Al-Ru’yah Antara Kitab Fatāwā Al-Subkī Oleh Taqī Al-Dīn Al-Subkī Dan Al-Fatāwā Al-Kubrā Oleh Ibn Taymiyyah: A Comparative Analysis of the Concept of Imkān al-Ru’yah between Kitab Fatāwā alSubkī by Taqī al-Dīn al-Subkī and Kitab alFatāwā al-Kubrā by Ibn Taymiyyah - Rahiman, Nurul Syakirah; Mohd Nawawi, Mohd Saiful Anwar; Abdul Wahab, Raihana (Jurnal Fiqh, 2021)
Taqī al-Dīn al-Subkī was a scholar proficient in the field of fiqh and usul al-fiqh while Ibn Taymiyyah was a leading Hanbali thinker. Among their works are Kitab Fatāwā al-Subkī and Kitab Fatawa al-Kubra. This study analyzes the comparison between the thoughts of Taqī al-Dīn al-Subkī and Ibn Taymiyyah on the concept of imkan al-ru’yah in determining the beginning of the month of hijrah. This is due to al-Subkī who accepted the concept of imkānalru’yah in the context of hisab as another method for the determination of the crescent moon, but which was rejected by Ibn Taymiyyah.This study adopts a qualitative approach and gathering of information is based on a content analysis of the two main books, namely Kitab Fatāwā al-Subkī and Kitab al-Fatāwā al-Kubrā. It is concluded that imkan al-rukyah had been discussed by both figures in their respective writings. Indeed, there is a clear difference in the acceptance of the concept of imkan al-rukyah.